Novel plasmid-mediated colistin resistance gene mcr-7.1 in Klebsiella pneumoniae - Yang, Yong-Qiang; Li, Yun-Xia; Lei, Chang-Wei; Zhang, An-Yun; Wang, Hong-Ning (Journal of antimicrobial chemotherapy, 2018)
Abstract Objectives To identify a novel plasmid-mediated colistin resistance gene in Klebsiella pneumoniae isolated from chickens in China. Methods WGS was used to identify a novel colistin resistance gene. The transferability of plasmids carrying mcr-7.1 was investigated by conjugation experiments. The expression of the mcr-7.1 gene was examined using an expression vector. Results A novel plasmid-mediated colistin resistance gene mcr-7.1, sharing 70% amino acid identity with the mcr-3 gene, was identified in three K. pneumoniae strains isolated from chickens in China. The mcr-7.1 gene was found in an IncI2-type plasmid (pSC20141012) that co-harboured the blaCTX-M-55 gene in one isolate. pSC20141012 can be transferred from K. pneumoniae SC20141012 to Escherichia coli J53Azr, exhibiting a ≥8-fold increase in colistin MIC compared with the recipient E. coli J53Azr. Conclusions We identified a novel plasmid-mediated colistin resistance gene named mcr-7.1 in K. pneumoniae in China. The prevalence of mcr-7.1 in various species of human and animal origin needs to be investigated immediately.